Preoperative patient risk factors for intraoperative hypotension: a systematic review and meta-analysis - Daum, Nils; Bill, Daniel; Thiele, Moritz; Felber, Julian; von Wedel, Dario; Spies, Claudia; Balzer, Felix; Mörgeli, Rudolf; Hunsicker, Oliver; Müller, Anika; Contag, Dennis; Pohrt, Anne; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIntraoperative hypotension (IOH) presents a risk factor for postoperative organ dysfunction. However, as a unique definition of IOH is still missing, the influence of individual preoperative patient characteristics on IOH remains poorly understood. This systematic review aimed to examine the variability in IOH definitions and to identify preoperative risk factors associated with IOH.MethodsA systematic literature search was conducted from inception to March 2, 2024. Studies reporting on IOH and from which the association between preoperative characteristics and IOH in cardiac and non-cardiac surgery could be derived were included. Odds ratios (ORs) were either extracted directly or calculated based on available patient-level data. Pooled estimates were generated using a random-effects model.ResultsOut of 7,361 screened studies, 78 met the inclusion criteria. Heterogeneity was high due to varying IOH definitions. 14 preoperative factors were included in the meta-analysis. Older age (OR 1.03, 95% CI 1.02–1.04) and female sex (OR 1.16, 95% CI 1.08–1.24) were associated with increased IOH risk. ASA-II was linked to lower risk compared to ASA-III (OR 0.80, 95% CI 0.70–0.91). Diabetes mellitus (OR 1.18, 95% CI 1.04–1.35) and arterial hypertension (OR 1.56, 95% CI 1.33–1.83) were independent predictors. ACE inhibitor use (angiotensin-converting enzyme inhibitor use; OR 1.63, 95% CI 1.42–1.88), angiotensin receptor blocker (ARB) use (OR 1.38, 95% CI 1.01–1.89), and emergent surgery (OR 1.25, 95% CI 1.09–1.42) also increased IOH incidence. The risk of bias was low to moderate.ConclusionThe substantial variability in IOH definitions and several preoperative IOH influencing patient characteristics highlight the need for standardized criteria to improve comparability and guide personalized perioperative management.Systematic Review Registrationidentifier PROSPERO CRD42024514229.